The Impact of Excess Capacity on the Investment Falloff - Artica, Rodrigo Pérez (Panoeconomicus, 2023)
I documented a widespread decline in the rate of capacity utilization in the US manufacturing industry during the last decades, which parallels a worsening trend of gross capital formation. I conducted several exploratory exercises to investigate whether utilization rates were actually related to the investment performance during 1952-2014. Vector auto-regressive estimates imply a non-trivial quantitative relationship between utilization rates and investment, which accounts for a decline equivalent to more than 30% of the average investment falloff over the whole period considered. Finally, I used firm-level data to control for other investment determinants. The relationship remains statistically and economically significant. In addition, I found a link between past accumulated utilization variation and current investment, suggesting that excess capacity could be a relevant force behind current investment weakness. JEL: E20, E22. Keywords: Investment, Capacity utilization.